Principals Instructional Leadership Role: The Case of International Schools in Sri Lanka - Kumari, H. M. Lalitha (International Journal on Integrated Education, 2023)
This study examines the instructional leadership (IL) role of international school principals in Sri Lanka. The main aim of this study was to identyfy how do principal’s play instructional leadership roles as instructional leader in international schools. The objevtives of the study were to find out principal’s role as instructional leader in international schools and to identify what activities principals engage in promoting the education of students and upgrading the pedagogy of teachers in international schools. The multiple case study method was used in the current study. Accordingly, Semi-structured interviews and focused group discussions were used as data collecting tools. As the study sample three principals, and nine teachers were selected using purposive sampling for interviews and group discussion. The study found that all principals in the sample success to balance their general administrative responsibilities and instructional leadership roles. All the principals in the sample mentioned that they implement innovative methodologies to promote the education of students and upgrading the pedagogy of teachers. The study further found that principals pay a significsnt attention on teachers professional devlopment, provision of instructional materials and incentives for teaching and learning by international schools principals as instructional leaders. It was further found that principals in international schools face difficulties in terms of retention of qualified trained teachers as a significant number of teachers (nearly 30%) are leaving the country. Therefore it is recommended that the international school principals need to be taken immediate action in order to retain qualified experienced teachers in their schools.